2021
DOI: 10.3389/fonc.2021.657615
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Biomarkers to Predict and Evaluate the Effectiveness of Immunotherapy in Advanced Non-Small-Cell Lung Cancer

Abstract: ObjectiveWe aimed to identify imaging biomarkers to assess predictive capacity of radiomics nomogram regarding treatment response status (responder/non-responder) in patients with advanced NSCLC undergoing anti-PD1 immunotherapy.Methods197 eligible patients with histologically confirmed NSCLC were retrospectively enrolled from nine hospitals. We carried out a radiomics characterization from target lesions (TL) approach and largest target lesion (LL) approach on baseline and first follow-up (TP1) CT imaging dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 50 publications
4
41
0
Order By: Relevance
“…Therefore, integrating radiomics features of NCE-CT and CE-CT images into a predictive panel as a radiomics model may be a robust approach for predicting response to immunotherapy. Compared our previous study (42), the combined-radiomics models based on only NCE/CE-CT images of baseline from the single largest lesion approach may be more promising for clinical application and early prediction.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, integrating radiomics features of NCE-CT and CE-CT images into a predictive panel as a radiomics model may be a robust approach for predicting response to immunotherapy. Compared our previous study (42), the combined-radiomics models based on only NCE/CE-CT images of baseline from the single largest lesion approach may be more promising for clinical application and early prediction.…”
Section: Discussionmentioning
confidence: 84%
“…The analysis of radiomic features one by one demonstrated that something changes within tumors after the introduction of immunotherapy, and these observations are confirmed by the trend of significant delta features that is mostly different in amplitude and direction in the three classes. To our knowledge, only three studies established a relationship between delta features and response to immunotherapy [ 7 , 22 , 23 ] and none tried to interpret radiomic features and their variations. Our study demonstrated that 27 delta features presented a similar trend and might be associated with a definite response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite most of published papers having focused on radiomic features at baseline, interesting evidence is also emerging from studies assessing changes in radiomic parameters over time, which seem to be associated with tumor response and survival [ 29 , 30 , 31 , 32 , 33 ]. For example, Khorrami et al [ 29 ] evaluated response to ICI by exploiting differences in CT radiomic features between baseline and after 3–4 cycles of immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, PFS was significantly shorter in patients with a high-risk nivolumab signature [ 31 ]. Nonetheless, Liu at al [ 32 ] developed a nomogram model based on delta radiomics signature, clinical variables, and PD-L1 status that was able to identify responders from non-responders with good accuracy (AUC of 0.83 in the training test).…”
Section: Resultsmentioning
confidence: 99%